DIGITALIZED-BASED SMALL ENTERPRISE TO ENHANCE HOUSEHOLD FINANCIAL INCOME IN POST-COVID-19: SRIHARJO VILLAGE, YOGYAKARTA - Dina Ruslanjari; Diana Puspitasari; Didik Hariyadi Raharjo (Republic of Indonesia Defense University, 2024)
COVID-19 hampered economic aspects, particularly financial deprivation of business around the globe. Small Medium Enterprise (SME) potentially encountered great impacts, e.g. bankruptcy and business closure. SMEs at Sriharjo Village searched for business opportunities to improve livelihoods and income during post-COVID-19. This study aimed to identify digitalized-based opportunities for economic improvement at the household level, investigate government roles in promoting SMEs through digitalization, and find out the escalation of household income. The research applied a qualitative approach, observational data collection, in-depth interviews, and documentation studies. The result of this study identified three characteristics of SME in post-COVID-19 Sriharjo: the business could survive during the pandemic; the escalation of women's entrepreneurship with new innovative products; and developing existing businesses with innovation. The local authority is involved in promoting the SME on a digital-based platform and providing training. The monthly profit of SME ranged from IDR 3 million to 10 million, which truly helped the community fulfilled its economic needs. Collaboration, innovation, training in digital platform among community members in leveraging digital-based opportunities are the keys to economic recovery following the pandemic. The activity successfully delivered additional education, skills in digital marketing, and economic resilience to small and medium-sized enterprises in the village.